Cross-Platform Analysis and Development of Online Catering Platform (Kunyahku) - Swarna, Indra; Purnama, James; Anthony, Randy (Journal of Applied Information, Communication and Technology, 2020)
Kunyahku is an online catering platform that provides catalogs of menus from local caterer near the user and become the distributor that will take the order and deliver them. In developing an application, the most important aspect for small start-up companies is to have a development stack that can deliver the app into multiple platform by using a single code base to reduce the cost of developers, improve efficiency and reduce the time to develop the application itself. To provide the necessity of building an application for Kunyahku, this paper is aimed to find the most suitable cross platform framework for developing the Kunyahku application. This research focuses on comparison between existing popular cross-platform and proving the suitable one to be used in development cycle in the case of Kunyahku requirements. Sets of test and comparison were conducted in order to compare the most suitable cross platform between React Native and Flutter such as render test and comparing each advantage coming out from using each of the cross-platform.After all the requirements are gathered and then the most suitable framework will be chosen which is Flutter. Performance analysis and the benefits of using Flutter framework are elaborated and thus proving it is the most suitable development stack to be used in Kunyahku case and the development time can be reduced since it is a cross-platform technology that output the application into three different platform rather than managing separate platform for each different one. Testing shows that flutter also met all the requirements thus proving flutter address the problems of scalability and faster development compared to developing each native platform one by one.